1991
DOI: 10.1099/00207713-41-1-148
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter nemestrinae sp. nov., a Spiral Bacterium Found in the Stomach of a Pigtailed Macaque (Macaca nemestrina)

Abstract: A new microaerophilic, spirally curved, rod-shaped bacterium was isolated from the gastric mucosa of a pigtailed macaque (Macaca nemestrina). The gram-negative cells of this bacterium are oxidase, catalase, and urease positive and strongly resemble Helicobacter pylon' (Campylobacter pylon) cells. Like H. pylon', this organism does not metabolize glucose, does not reduce nitrate or produce indole, does not produce H,S from triple sugar iron agar, does not hydrolyze hippurate or esculin, and does not grow in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 33 publications
1
34
1
Order By: Relevance
“…At present, the reason for the discrepancy between our data and the data published by Bronsdon et al (1991) and Sly et al (1993) is unclear. The 16S rDNA sequencing results were reproduced with a sample of ATCC 49396 T grown from a ' seed vial ' that was kindly provided by the ATCC and had been produced in the initial deposition process in 1990.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…At present, the reason for the discrepancy between our data and the data published by Bronsdon et al (1991) and Sly et al (1993) is unclear. The 16S rDNA sequencing results were reproduced with a sample of ATCC 49396 T grown from a ' seed vial ' that was kindly provided by the ATCC and had been produced in the initial deposition process in 1990.…”
contrasting
confidence: 55%
“…The beststudied of these is Helicobacter pylori, a prevalent human pathogen that colonizes the gastric mucus of more than half of the human population and causes chronic, often lifelong infections. Helicobacter nemestrinae T81213-NTB T (l ATCC 49396 T ) was isolated from a pigtailed macaque (Macaca nemestrina) and has been reported to be closely related to H. pylori (Bronsdon et al, 1991 The GenBank/EMBL/DDBJ accession numbers for the sequences reported in this paper are AJ421784-AJ421792.…”
mentioning
confidence: 99%
“…mustelae, H. felis, H. suis, H. nemestrinae and H . heilmannii Fox & Lee, 1989;Bronsdon et al, 1991;Paster et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…pylori was, therefore, transferred to the new genus and renamed as Helicobacter pylori. The major features [15,29] of Helicobacter genus consist of Helical, curved or straight unbranched morphology.…”
mentioning
confidence: 99%